2012
DOI: 10.1038/npp.2012.167
|View full text |Cite
|
Sign up to set email alerts
|

Heroin Self-Administration Experience Establishes Control of Ventral Tegmental Glutamate Release by Stress and Environmental Stimuli

Abstract: Heroin and cocaine have very different unconditioned receptor-mediated actions; however, in the brain circuitry of drug-reward and motivation, the two drugs establish common conditioned consequences. A single experience with either drug can change the sensitivity of ventral tegmental area (VTA) dopamine neurons to glutamatergic input. In the case of cocaine, repeated intravenous selfadministration establishes de novo VTA glutamate release and dopaminergic activation in response to conditioned stimuli and mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Wang et al (2012) reported that footshock-induced reinstatement of heroin seeking is associated with increased glutamate (and dopamine) release in VTA, and that local blockade of ionotropic glutamate receptors prevents this reinstatement. These data extend previous results with cocaine-trained rats (Wang et al 2005).…”
Section: Recent Neurobiological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al (2012) reported that footshock-induced reinstatement of heroin seeking is associated with increased glutamate (and dopamine) release in VTA, and that local blockade of ionotropic glutamate receptors prevents this reinstatement. These data extend previous results with cocaine-trained rats (Wang et al 2005).…”
Section: Recent Neurobiological Findingsmentioning
confidence: 99%
“…Basolateral amygdala: Food deprivation : heroin (Tobin et al 2013). VTA: Footshock: cocaine (McFarland et al 2004; Wang et al 2005), heroin (Wang et al 2012); Swim stress: (Graziane et al 2013). Median Raphe: Footshock: alcohol (Le et al 2002); y ohimbine: alcohol (Le et al 2012).…”
Section: Figurementioning
confidence: 99%
“…VTA glutamatergic signaling is also associated with conditioned rewarding effects. VTA glutamate levels, measured by microdialysis in rats self-administering intravenous cocaine (You et al, 2007) or heroin (Wang et al, 2012), increase following conditioned cues for the drug, but not following unconditioned drug exposure.…”
Section: Mesopontine Cholinergic and Glutamate Neurons Activate Damentioning
confidence: 99%
“…In animals trained to self-administer cocaine or heroin, response-contingent presentations of drug availability cues cause release of the neurotransmitter glutamate in the ventral tegmental area (You et al, 2007a; Wise et al, 2008; Wang et al, 2012) and in the nucleus accumbens (NAS) (LaLumiere and Kalivas, 2008; Suto et al, 2010: also see Hotsenpiller et al, 2001); glutamatergic input to each of these brain regions can cause renewal of responding after apparent extinction of the response tendency (Cornish et al, 1999; Suto et al, 2004; Wang et al, 2005; Wang et al, 2012). …”
Section: Introductionmentioning
confidence: 99%